Innovative Strategies to Improve the Clinical Application of NK Cell-Based Immunotherapy - Tarannum, Mubin; Romee, Rizwan; Shapiro, Roman M. (Frontiers in Immunology, 2022)
Natural killer cells constitute a part of the innate immune system that mediates an effective immune response towards virus-infected and malignant cells. In recent years, research has focused on exploring and advancing NK cells as an active immunotherapy platform. Despite major advances, there are several key challenges that need to be addressed for the effective translation of NK cell research to clinical applications. This review highlights some of these challenges and the innovative strategies being developed to overcome them, including in vitro expansion, in vivo persistence, infiltration to the tumor site, and prevention of exhaustion.